Concentrations of heavy metals in different tissues of the bivalve Polymesoda erosa: its potentials as a biomonitor and food safety concern - Yap, Chee Kong; Edward, Franklin Berandah; Tan, Soon Guan (Universiti Putra Malaysia Press, 2014)
Three populations of Polymesoda erosa collected from the west coast of Peninsular Malaysia were analyzed for heavy metals. Their soft tissues were dissected into muscle, foot, mantle, gill and remaining soft tissues (remainder). Overall metal concentrations (Âµg/g dry weight) in five soft tissues of the three clam populations were Cd (0.25-2.86), Cu (1.80- 21.0), Ni (0.66-30.0), Pb (0.94-7.09), and Zn (79.2-365), and these were Cd (3.64-7.07), Cu (2.37-3.29), Ni (26.2-30.0), Pb (58.8-61.6), and Zn (3.84-8.78) for the shell ranges. Among the three Polymesoda populations, gill was found to have accumulated higher Cu and Zn concentrations compared to other soft tissues, whereas shell was found to have high levels of non-essential Cd, Pb and Ni. Information on heavy metals obtained in this study could serve as baseline data for this particular species since the information is lacking in the literature. The present study has evidently shown that different soft tissues of P. erosa are potential biomonitoring for Cd, Cu, Ni and Zn, whereas the clam shell as a potential biomonitoring material for Pb based on: (1) positive results based on biota-sediment accumulation factors (BSAF) (being macroconcentrators), (2) positive and significant correlations of metals between all five soft tissues (foot, gill, mantle, muscle and remainder) and the sedimentary geochemical fractions and total metal concentrations, and (3) comparisons to two similar burrowing bivalves (Donax faba and Gelonia expansa). Regardless of some metals in edible soft tissues having exceeded the food safety permissible limits, the concentrations of Cd, Cu, Ni and Zn in the soluble fractions (which is more bioavailable to consumers) of all the five edible soft tissues of P. erosa are below all the permissible metal limits. Therefore, these estimations clearly showed that the consumption of P. erosa could pose no toxicological risks to consumers.